Gα12 ablation exacerbates liver steatosis and obesity by suppressing USP22/SIRT1-regulated mitochondrial respiration - Tae Hyun Kim; Yoon Mee Yang; Chang Yeob Han; Ja Hyun Koo; Hyunhee Oh; Su Sung Kim; Byoung Hoon You; Young Hee Choi; Tae-Sik Park; Chang Ho Lee; Hitoshi Kurose; Mazen Noureddin; et al. (The Journal of Clinical Investigation, 2018)
Nonalcoholic fatty liver disease (NAFLD) arises from mitochondrial dysfunction under sustained imbalance between energy intake and expenditure, but the underlying mechanisms controlling mitochondrial respiration have not been entirely understood. Heterotrimeric G proteins converge with activated GPCRs to modulate cell-signaling pathways to maintain metabolic homeostasis. Here, we investigated the regulatory role of G protein α12 (Gα12) on hepatic lipid metabolism and whole-body energy expenditure in mice. Fasting increased Gα12 levels in mouse liver. Gα12 ablation markedly augmented fasting-induced hepatic fat accumulation. cDNA microarray analysis from Gna12-KO liver revealed that the Gα12-signaling pathway regulated sirtuin 1 (SIRT1) and PPARα, which are responsible for mitochondrial respiration. Defective induction of SIRT1 upon fasting was observed in the liver of Gna12-KO mice, which was reversed by lentivirus-mediated Gα12 overexpression in hepatocytes. Mechanistically, Gα12 stabilized SIRT1 protein through transcriptional induction of ubiquitin-specific peptidase 22 (USP22) via HIF-1α increase. Gα12 levels were markedly diminished in liver biopsies from NAFLD patients. Consistently, Gna12-KO mice fed a high-fat diet displayed greater susceptibility to diet-induced liver steatosis and obesity due to decrease in energy expenditure. Our results demonstrate that Gα12 regulates SIRT1-dependent mitochondrial respiration through HIF-1α–dependent USP22 induction, identifying Gα12 as an upstream molecule that contributes to the regulation of mitochondrial energy expenditure.